2010
DOI: 10.2202/1944-4079.1036
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Social Science Research on High‐Level Nuclear Waste: Achievements and Future Challenges

Abstract: Research on high‐level nuclear waste management has focused on technical and scientific issues since the U.S. National Academy of Sciences first studied the problem in the mid‐1950s and recommended long‐term disposal in deep salt formations. In this review, we trace the development of the problem's definition and its associated research since socioeconomic, political, and policy issues were first given consideration and nuclear waste management became recognized as more than a technical problem. Three somewhat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 103 publications
1
14
0
Order By: Relevance
“…Social scientists can also assist in communications regarding the technical aspects of UNF storage to the public and help to “frame policy in terms and values that matter most to the public” (Bonano et al, , p. 13). As nuclear energy issues move from being centered on technical knowledge to encompassing social and ethical implications, collaborations between policymakers and social scientists become more salient (Solomon et al, ).…”
Section: Nuclear Energymentioning
confidence: 99%
“…Social scientists can also assist in communications regarding the technical aspects of UNF storage to the public and help to “frame policy in terms and values that matter most to the public” (Bonano et al, , p. 13). As nuclear energy issues move from being centered on technical knowledge to encompassing social and ethical implications, collaborations between policymakers and social scientists become more salient (Solomon et al, ).…”
Section: Nuclear Energymentioning
confidence: 99%
“…It is the background of this research that made the anti-nuclear movement take a critical stance towards social scientists, as many activists considered the role of these researchers to be 'acceptance brokers' working for the nuclear industry. From the mid-1990s onwards and against the backdrop of many failed disposal projects worldwide, social scientists have broadened their perspectives and have taken into consideration ethical questions (for instance intergenerational justice) and alternative disposal options (like multi-national repositories) (Salomon et al 2010). Interconnections between research axes and political interests have also become a topic of social scientists' work (for instance : Macfarlane 2003).…”
Section: S10mentioning
confidence: 99%
“…While the safety of deep GD has been the predominant domain of science and engineering, the acceptability of and participative approaches to siting disposal facilities has been the domain of the social sciences. Within this field of social-science research on high-level nuclear waste, Solomon et al (2010) identified three overlapping time periods. In the latter, since the mid-1990s, research has largely dealt with public participation, political systems and international solutions, as well as risk perception and siting conflicts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%